2017
DOI: 10.1631/jzus.b1600109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neuron-related genes for cell therapy of neurological disorders by network analysis

Abstract: Bone mesenchymal stem cells (BMSCs) differentiated into neurons have been widely proposed for use in cell therapy of many neurological disorders. It is therefore important to understand the molecular mechanisms underlying this differentiation. We screened differentially expressed genes between immature neural tissues and untreated BMSCs to identify the genes responsible for neuronal differentiation from BMSCs. GSE68243 gene microarray data of rat BMSCs and GSE18860 gene microarray data of rat neurons were rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The activation of CREB promotes the transcription of many genes associated with neuronal survival, cell differentiation and axonal growth (Freitas et al, 2013). In our previous study, we showed that CREB1 plays pivotal roles in neuronal differentiation (Su et al, 2017a). In our present study, the results showed that CREB1 plays pivotal roles in the negative regulation of axons.…”
Section: Discussionsupporting
confidence: 58%
“…The activation of CREB promotes the transcription of many genes associated with neuronal survival, cell differentiation and axonal growth (Freitas et al, 2013). In our previous study, we showed that CREB1 plays pivotal roles in neuronal differentiation (Su et al, 2017a). In our present study, the results showed that CREB1 plays pivotal roles in the negative regulation of axons.…”
Section: Discussionsupporting
confidence: 58%
“…While any diffuse hyperinflammation corrected by PLT cytokine use is welcome, numerous CNS signal pathways are impacted upon PLT activation to facilitate tissue repair, angiogenesis and neurogenesis [84]. This work therefore expands prior descriptions of PRP treatment for CNS disorders [7] given its recuperative effects in SCI and peripheral nerve damage documented elsewhere [68,85]. This approach also extends earlier PRP use in kidney disease, which balanced difficulties of treating an encapsulated solid organ with the need to dose PRP locally [86].…”
Section: Discussionmentioning
confidence: 70%
“…AHP's data requirement is relatively low and depends more on operator's personal thinking and experience. It decomposes every hierarchy of elements related to decision-making stepwisely and calculates the final decomposed elements' weights based on the two elements' importance 3,[12][13][14] . Lei 3 proposed an AHP-based Fuzzy Comprehensive Evaluation Model in the light of the construction of the emergency LSC of People's Armed Police Force dealing with mass emergencies.…”
Section: Fuzzy Comprehensive Evaluation Modelmentioning
confidence: 99%